Harvesting the fruits : aspects of Christian faith in ecumenical dialogue - Kasper, Walter, 1933- (Continuum, 2009)
The Second Vatican Council declared the restoration of unity among Christians to be one of its principal concerns. Division among the Churches scandalises the world and damages that most holy cause, the preaching of The Gospel to every creature. A key figure to have worked tirelessly at these aims is Cardinal Walter Kasper, one of the most experienced, authoritative, and respected members of the Vatican hierarchy. Here Cardinal Kasper summarises the results of the Catholic Church's official dialogues with Lutheran, Reformed, Anglican and Methodist Churches over forty years, sets out a blueprint for 'consensus and convergence', and sets out a map for the way forward for ecumenism. From such a source, this document is therefore of crucial importance. The book focuses on the major issues in ecumenical dialogue - Jesus Christ, The Holy Trinity, Justification, The Church and The Sacraments of Baptism and Eucharist. Cardinal Kasper explains the key issues at stake and offers signposts for the way forward so that the wish of Jesus may be fulfilled: That They May All Be One.